Synthesis and Characterization of Nickel Oxide Nanoparticles - Gupta, Sakshi (My University, 2011)
Nanoparticles of NiO are prepared by thermal decomposition of freshly prepared nickel hydroxide by a sol gel route at 300 0C. This sample is characterized by x-ray diffractometer and vibrating sample magnetometer. The average crystallite size is found to be about 5 nm. The prepared nanoparticles of NiO are found to be antiferromagnetic at room temperature.
M.Sc. (Physics)
Keywords: Naroparticles; Magnetization